Pengaruh Tayangan Drama Korea Itaewon Class terhadap Motivasi menjadi Entrepreneurship - Salma Putri Hadiyani; Zainal Abidin; Wahyu Utamidewi (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
ABSTRACT: This study aims to determine the effect of the message content of Korean dramas and the influence of the characteristics of the role of Park Saeroyi who works hard in opening a business and doing business in the Korean drama series "Itaewon Class" on motivational behavior to become entrepreneurship. The researcher uses the uses and effect theory with variables adjusted to the "Itaewon Class" show, which is classified into indicators of Intensity, Message Content, and Attractiveness. The analysis technique used in this study is an explanatory analysis technique with classical assumptions and simple regression analysis, which is a form of research based on data collected during systematic research from the object under study by combining the relationships between the variables involved using a questionnaire as the main instrument for collecting data. , with a total of 66 respondents. The results of this study indicate that respondents get positive results or effects from the media, namely "Itaewon Class" in all indicators with the dominant indicator being Message Content and Attractiveness, and unexpected effects occur in the Intensity indicator. The results are generally stated that respondents get the influence of the Korean drama "Itaewon Class" and have the motivation to become entrepreneurship. Keywords: Itaewon Class Korean Drama, Motivation and Entrepreneurship